Phenotypic Changes in Subpopulations of Human NK and NKT Cells Induced - T. P. Smolina; T. A. Kuznetsova; L. A. Ivanushko; A. K. Gazha; A. S. Silchenko; N. N. Besednova (Антибиотики и Химиотерапия)
The article studies the effect of sulfated polysaccharide extracted from brown algae Fucus evanescens(fucoidan) and the product of its enzymatic transformation on human NK and NKT cells. Significant phenotypic changes in NK and NKT cells were recorded as a result of incubation of whole blood with polysaccharides. This was manifested in an increase in the expression of the activation molecules CD69, CD25, HLA-DR and the degranulation marker CD107a on NK and NKT cells, as well as CD8 molecules on NK cells. The effect of the enzymatic transformation product was significantly more pronounced compared to the native polysaccharide only in relation to the expression of CD69.